In vitro deposition of the respirable fraction of dry powder inhalations determined by laser diffractometry and inertial impaction - Marques, Helena (2015)
Particle size analysis of drug and excipient is of particular interest for dry powder inhalation (DPI) formulations development and quality control. In this work, the deposition in the upper, the medium and the lower (i.e. the respirable fraction) Twin Impinger compartments of sodium cromoglycate (SCG), lactose (as excipient) and a 1: 1 mixture thereof was determined by chemical analysis using a DPI device - the Micro-haler(TM) - and compared with the results obtained by laser diffractometry for the same fractions. The analytical method for the SCG determination consisted of ultraviolet spectrophotometry and, for the lactose, high performance liquid chromatography with refractive index detection was used. Laser diffractornetry as a quickly operating routine method can substitute the chemical analysis in order to evaluate the respirable fraction, under the conditions of the present work and therefore making formulation development easier and quicker.